PARTISIPASI PETANI DALAM PROGRAM UPSUS PAJALE DI KECAMATAN RAWA JITU SELATAN KABUPATEN TULANG BAWANG - Destika Maulidiawati; Dewangga Nikmatullah; Rio Tedi Prayitno (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
This study aims to examine the implementation, the level of farmers’ participation, and factors related to the level of participation in the Upsus Pajale program in South Rawa Jitu Sub-District of Tulang Bawang Regency.  This study data was collected in January-February 2017 by envolving 54 farmers’ respondents.  This study was conducted by survey method and its data was analyzed descriptively and statistically by Rank Spearman Correlation.  The results showed that factors related to farmers’ participation in Upsus Pajale Program were production, group communication behavior and intensity of program socialization.  Farmers' participation in planning activity was mostly (59,26%) in moderate category, participation in implementation activity was mostly (83,3%) in high category, participation in monitoring and evaluation activities was low (46,3%) and participation in the utilization of development outcomes was high (100%). In overall, most of farmers' participation in Upsus Pajale program in Rawa Jitu Selatan sub District wass moderate (48,15%) .Key words: farmer, participation, Upsus Pajale